Dual inhibition of PI3K/mTOR signaling in chemoresistant AML primary cells. (May 2018) - Bertacchini, Jessika; Frasson, Chiara; Chiarini, Francesca; D'Avella, Daniele; Accordi, Benedetta; Anselmi, Laura; Barozzi, Patrizia; Foghieri, Fabio; Luppi, Mario; Martelli, Alberto M.; Basso, Giuseppe; Najmaldin, Saki; et al.
Abstract: A main cause of treatment failure for AML patients is resistance to chemotherapy. Survival of AML cells may depend on mechanisms that elude conventional drugs action and/or on the presence of leukemia initiating cells at diagnosis, and their persistence after therapy. MDR1 gene is an ATP-dependent drug efflux pump known to be a risk factor for the emergence of resistance, when combined to unstable cytogenetic profile of AML patients. In the present study, we analyzed the sensitivity to conventional chemotherapeutic drugs of 26 samples of primary blasts collected from AML patients at diagnosis. Detection of cell viability and apoptosis allowed to identify two group of samples, one resistant and one sensitive to in vitro treatment. The cells were then analyzed for the presence and the activity of P-glycoprotein. A comparative analysis showed that resistant samples exhibited a high level of MDR1 mRNA as well as of P-glycoprotein content and activity. Moreover, they also displayed high PI3K signaling. Therefore, we checked whether the association with signaling inhibitors might resensitize resistant samples to chemo-drugs. The combination showed a very potent cytotoxic effect, possibly through down modulation of MDR1, which was maintained also when primary blasts were co-cultured with human stromal cells. Remarkably, dual PI3K/mTOR inactivation was cytotoxic also to leukemia initiating cells. All together, our findings indicate that signaling activation profiling associated to gene expression can be very useful to stratify patients and improve therapy.